Kegiatan Bakti Sosial untuk Masyarakat Miskin di Wilayah Pesisir Kabupaten Karawang - Nopiana, Medi; Nurhanifah, Afifa; Nasution, Raden; Muhammad, Rabhi Fathan; Wiliyanti, Rizke (Politeknik Negeri Samarinda, 2025)
The coastal communities of Karawang Regency are still facing poverty issues. Therefore, the community service team carried out community service activities in social service. Sedari Village, Cibuaya Subdistrict, was the location for social service activities. In addition to the Sedari Village Government and its staff, this activity involved students in encouraging empathy, concern, and support for coastal communities, especially in the village. This activity encountered several obstacles, especially regarding road access to the social service location, considering that the activity was carried out during the rainy season. The implementation of this social service was appreciated by the Sedari Village Government, especially the Tanjungsari Hamlet apparatus, its staff, and the local community because this activity still needs to be carried out in their area. Activities to ease the burden on people experiencing poverty not only rely on government programs but also require the role and contribution of stakeholders in the Karawang Regency area, including Universitas Singaperbangsa Karawang.